Incorpórese al Código Orgánico Integral Penal un nuevo tipo penal respecto al reclutamiento de niños, niñas y adolescentes para conformar escuelas de sicariato. - Reinosa Patiño, Ronny Ramiro (2024)
This research work entitled "INCORPORATE INTO THE INTEGRAL CRIMINAL ORGANIC CODE A NEW CRIMINAL TYPE REGARDING THE RECRUITMENT OF CHILDREN AND ADOLESCENTS TO FORM SICARITY SCHOOLS", Ecuador has become a state of conflict, instituted by different national and foreign criminal gangs in the provinces of Manabí, Guayas and the northern border of the country. The interest in developing this thesis is due to the legal vacuum and the need that exists in the Organic Integral Penal Code for not having a custodial sentence for the leaders who recruit children and adolescents for the formation of schools of assassination by criminal groups in the struggle for power within Ecuadorian territory and the distribution of controlled substances "cocaine" to different parts of the country and international territory, since Article 370 of the Organic Integral Penal Code on Illicit Association does not specify this activity as a criminally relevant conduct, as it directly affects the main fundamental rights established in the Constitution of the Republic of Ecuador, the Code of Children and Adolescents and International Child Protection Law. Thanks to the contribution of different legal specialists, it has been possible to justify that by not integrating into Ecuadorian criminal law the crime of illicit recruitment of children and adolescents to form schools of hired assassination, constitutional rights such as the principle of integral development and ensuring the full exercise of their rights are being violated. the right of persons and groups of priority attention, the right to life, the right to physical, psychological and moral integrity, to social security; to have a family and enjoy family and community life; to social participation; to respect for their freedom and dignity. In early civilisations such as Rome, the word and actions of the hitman were conceptualised as the person in charge of murder in exchange for a monetary benefit. Thirty surveys were carried out and ten interviews were conducted with different criminal law professionals such as prosecutors, judges and lawyers, as well as an interview with a fourteen-year-old adolescent victim of illegal recruitment by these criminal groups. The results were used for the legal reform project of article 370 of the Organic Integral Penal Code to include the crime of recruitment of children and adolescents for the creation of schools of hired assassination within Ecuadorian territory.